A Survey of the Quality of Salt Cured Fish Produced in the Kanyakumari District, Madras State - SRINIVASAN, R.; JOSEPH, K. C. (Fishery Technology, 1966)
A survey of the quality of salt cured fish in Kanyakumari District, Madras State was done during the years 1963 and 1964 to obtain necessary basic information to formulate quality standards for these products which are gaining importance in the export trade. 155 trade samples of sun-dried, dry-salted, wet-cured and pit-cured fishery products were examined for their chemical quality and organoleptic characteristics. 26.5% of the sun-dried products, 25% of the wet cured fish, 55.21% of the dried salted products and none of the pit cured samples were found to be good in quality. The sun dried products were generally found to have heavy admixture of sand and were inadequately dried. The chief defects in the salt cured fish products were found to be the use of spoiled fish, imperfect cleaning and washing, use of impure salt, inadequate salting, curing and drying, and unhygienic conditions in all stages. Quality standards must be formulated for each variety of salt cured fish product and adequate measures taken to rectify the defects and enforce the quality standards.